Creep Failure - The Natures Insidious Plight - Nasrul Azuan, Alang (Faculty of Mechanical & Automotive Engineering Technology, 2021)
To this day, it may have not dawned on you as significant whenever the phrase of creep failure is uttered about, but are you cognizant that we should particularly care about it for it’s prevalent, yet inherently implicit a phenomenon occurring to daily materials around our lives?